Investigating The Use Of Islamic Based Relationship Marketing Approach In Selected Malaysia Takaful Companies - Yusoff, Murni (2017)
The emergence of relationship marketing (RM) has commonly been connected to the financial services industry. In Islamic financial services industry, particularly Takaful is implementing the RM in various creative ways. Regrettably, the issue of unethical marketing practices seems to be the main contributors to the surrender of policy among Takaful participants in Malaysia. Therefore, this research intends to explore the issue from the root which derives from the worldview and epistemology embedded in RM by investigating the RM approach implemented in Takaful companies. The differences in worldview and epistemology have lead to different practices in reality of business.